PET imaging of tumor associated macrophages using mannose coated (64)Cu liposomes - Locke, Landon W. (Biomaterials, 2012)
Macrophages within the tumor microenvironment (TAMs) have been shown to play a major role in the growth and spread of many types of cancer. Cancer cells produce cytokines that cause macrophages to express scavenger receptors (e.g. the mannose receptor) and factors that facilitate tissue and blood vessel growth, suppress T cell mediated anti-tumor activity, and express enzymes that can break down the extracellular matrix, thereby promoting metastasis. We have designed a mannosylated liposome (MAN-LIPs) and show that it accumulates in TAMs in a mouse model of pulmonary adenocarcinoma. These liposomes are loaded with (64)Cu to allow tracking by PET imaging, and contain a fluorescent dye in the lipid bilayer permitting subsequent fluorescence microscopy. We injected these liposomes into a mouse model of lung cancer. In vivo PET images were acquired 6 h after injection followed by the imaging of select excised organs. MAN-LIPs accumulated in TAMs and exhibited little accumulation in remote lung areas. MAN-LIPs are a promising new vehicle for the delivery of imaging agents to lung TAMs. In addition to imaging, MAN-LIPs hold the potential for delivery of therapeutic agents to the tumor microenvironment.